Expression of CD5, CD1 0, Bcl-2 and Bcl-6 in diffuse large B cell lymphoma based on International Prognostic Index - Indrawati Tody Guntersah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: Diffuse large B cell lymphoma is the most common type of non-Hodgkin lymphoma. This tumor has heterogeneous clinical feature, morphology, genetic and molecular alterations. Diffuse large B cell lymphoma with a germinal centre ( GC ) pattern of gene expression including CD10 and Bcl-6 has a more favorable outcome. CD5 and Bcl-2 expression has been shown to have an adverse effect on the outcome in diffuse large B cell lymphomaObjective: To investigate the difference of CD5, CDlO, Bcl-2 and Bcl-6 expression based on International Prognostic Index IIPI) in diffuse large B cell lymphomaMethods: Fourty five cases of B cell diffuse large B cell lymphoma from embedding parafin tissue were constituted the basis of the study. Immunohistochemical examination using CD20, CD5, CD10, Bcl-2 and Bcl-6 monoclonal antibody was done. The difference of CD5, CD10, Bcl-2 and Bcl-6 expression between high and low IPI of diffuse large B cell lymphoma were analized by chi square testResult: There Vlias significant difference between the number of cases with positivity of CD5 and CD10 expression in high and low IPI of diffuse large B cell lymphoma. The result supported that immunophenotyping related B cell differentiation can help to predict clinical behavior and prognosis in diffuse large B cell lymphoma.Conclusion: Conclusion: There was significant difference between the number of cases with positivity of CD5 and CD10 expression in high and low IPI of diffuse large B cell lymphoma. The result supported that immunophenotyping related B cell differentiation can help to predict clinical behavior and prognosis in diffuse large B cell lymphoma.Key words : diffuse large B cell lymphoma, CD5, CD 10, IPI